Optimasi Sistem Antrian Digital Terintegrasi Fitur Chat pada Layanan Kelurahan Gebang Putih Berbasis User-Centered Design - Adam Shidqul Aziz; Nur Rosyid Mubtadai; Desy Intan Permatasari; Ferry Astika Saputra; Iwan Syarif; Arna Fariza; M. Udin Harun Al Rasyid; Nana Ramadijanti; Irwan Sumarsono; Ahmad Syauqi Ahsan; Umi Sa'adah; Andhik Ampuh Yunanto; Selvia Ferdiana Kusuma; Grezio Arifiyan Primajaya; Renovita Edelani; Asy Syaffa Khoirunnisa; Adam Ghazy Al Falah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Digital transformation in the public sector has encouraged the development of queuing systems that not only organize service flows but also provide faster and more accurate access to information for citizens. Gebang Putih Urban Village, a community partner of the Electronic Engineering Polytechnic Institute of Surabaya (PENS), implemented a digital queuing system based on Android and web platforms in 2024; however, the system still had limitations in terms of responsiveness and communication channels with citizens. This community service activity focuses on the technical optimization of the queuing system by integrating a chat-based interaction feature into the mobile application and simplifying the queue number retrieval flow through conversational interaction. The system was developed using a User-centered design (UCD) approach, with key stages including needs analysis based on the evaluation of the previous system, design of a new system architecture, implementation of chat integration, and internal testing with urban village officers as key users. The optimization results cover three main technical aspects: (1) integration of the chat service module into the mobile application without modifying the core queuing logic, (2) a queue number retrieval feature via chat that is directly connected to the digital queuing module, and (3) a two-way chat channel between citizens and officers facilitated through a web-based dashboard. Internal trials indicate improvements in service workflows, reduced face-to-face interactions for simple inquiries, and increased staff understanding of how to use the digital system. From a community engagement perspective, this work represents a development and capacity-building phase that strengthens officers’ ability to manage technology-based services and provides a technical foundation that is ready to be disseminated and replicated in other urban villages with minimal adaptation.